AB0171 B cell subpopulations in lupus nephritispatients: correlations with disease onset and outcomes. (12th June 2018) - Varriano, V.; Petricca, L.; Tolusso, B.; Costanzi, S.; Maria Rita, G.; Paglionico, A.; Di Mario, C.; Tanti, G.; Vischini, G.; Gambaro, G.; Ferraccioli, G.; Gremese, E.
Abstract : Background: the relationship between B cells subsets distribution, clinical and laboratory parameters, therapeutic response and prognosis in lupus nephritis (LN) is still underestimated. Objectives: The aim of our study is to establish the value of B cells subsets as biomarkers in patients with active LN than controls, in patients at the onset of renal manifestation than patients with renal flare, and finally in nephritic patients in relation to their clinical and laboratory characteristics at the baseline and during the course of the disease. Methods: 50 patients with a diagnosis of LN have been evaluated every tree months. Laboratory, immunological and disease activity data were collected at the baseline and at 6 (T6), 12 (T12), 24 (T24), 36 (T36) months and at the last follow-up (FU). Number of renal flares, time to renal remission and persistent proteinuria at the last FU were evaluated. B cell subsets were obtained through cytofluorimetry and classified using C27/IgD classification. The characterisation of B cells subsets was realised in 50 LN patients and 37 healthy controls. Results: LN patients had a lower percentage of CD19 +cells than controls (9.2% vs 10.6%; p=0.01) as well as a lower percentage of memory unswitched cells CD27 +IgD+ (10.7% vs 15.3%; p<0.001) while patients had an higher percentage of plasmablasts and double negative memory cells CD27-IgD- (respectively 5.9% vs 1%; p<0.001% and 10.9% vs 4.1%; p=0.01). No significant differences regardless B cells subsets were found between early LN patients and long ones as well as between LN patients at the onset and LN patients during renal flare. We found a correlation between an higher disease activity (assessed with SLEDAI 2K) and lower percentage of memory B cells IgD-CD27+ (p=0.02). Double negative B cells CD27-IgD- tended to be correlated with an higher disease activity. Of interest the correlation between persistent proteinuria detected during the follow-up and a lower percentage of plasmablasts at the baseline (p=0.01). Conclusions: The alteration of B cells subsets is an early event in LN without differences regardless the period of renal involvement (nephritic onset or later LN development). The association between persistent proteinuria and a lower percentage of plasmablasts at the baseline could be a negative prognostic factor considering the correlation between persistent proteinuria and worse renal outcome. Disclosure of Interest: None declared